Alliance Coordination: Explaining the Logic of Biden's Taiwan Policy. (19th December 2022) - Ye, Xiaodi
Abstract : The Biden administration is attempting to transform traditional US–Taiwan relations into a multilateralism‐based "US + alliance–Taiwan" interactional model, which can be conceptualized as alliance coordination . This article unpacks the logic of Biden's strategic thinking in the US Taiwan policy. Adopting an asymmetric alliance perspective, it argues that US allies' reactions to Biden's foreign policy and their ideological attitude toward China have interacted with the US placement of the Taiwan question on the agenda in the alliance system to produce different degrees of alliance coordination, which can be measured by the new typology constituted by seven approaches: all‐fields approach, pure high politics approach, high politics driven approach, half‐measures, low politics driven approach, pure low politics approach, and strategic inaction . Three cases, including the different reactions of Japan, European countries, and South Korea, are analyzed to demonstrate how the alliance coordination operates in realpolitik. Additionally, the assessment of this article reveals that Biden's alliance coordination would place growing strategic pressure on mainland China and introduces greater volatility into cross‐strait relations.